A Multimodal Analysis of Picture Books for Children: A Systemic Functional Approach - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Reviewed by Mary Frances Litzler Universidad de Alcalá, Spain   This book is a study of nine picture books for children ranging in age from 0 to 9 years old. The conceptual framework follows Halliday's Systemic Functional Grammar (2004) (henceforth, SFG) and Kress and van Leeuwen's Visual Social Semiotics (2006) (henceforth, VSS). The main objective is to "identify the verbal and visual strategies used by writers and illustrators... to convey a representation of reality, to create interaction with child-readers and to form coherent wholes of communication" (257).